Preventive and curative effects of Calendula officinalis infusion in a dextran sulfate sodium (DSS)-induced colitis model in BALB/c mice - Bouferkas, Youcef; Haddi, Abir; Amier, Leila; Argungu, Kabir Khadija; Belkaaloul, Kawthar; Addou, Samia (Archives of Biological Sciences, 2025)
Paper description: Calendula officinalis (Co) is known for its anti-inflammatory properties; its effects in the experimental model of dextran sulfate sodium (DSS)-induced colitis have not been thoroughly investigated. Experimental colitis was induced in BALB/c mice with 4% DSS administration for 7 days. Mice were divided into control, DSS-treated controls, and two groups receiving Co infusion (preventive and curative). Clinical signs, colon length, and inflammatory markers were assessed. Both preventive and curative Co treatments reduced weight loss, colonic damage, and pro-inflammatory cytokines. This study demonstrates Co’s dual potential as a preventive and curative treatment for colitis. Abstract: Inflammatory bowel disease (IBD), including ulcerative colitis and Crohn’s disease (CD), is characterized by chronic intestinal inflammation. Current therapeutic strategies, including immunosuppressants and biologics, have limitations such as adverse effects and variable efficacy. Calendula officinalis (Co), a medicinal plant with recognized anti-inflammatory and antioxidant properties, may represent a promising alternative or complementary approach. This study aimed to evaluate the preventive and curative effects of Co infusion in a murine model of ulcerative colitis (UC) induced by dextran sodium sulfate (DSS). Fifty male BALB/c mice were randomly assigned to five groups: control, DSS+water (positive), Co+DSS (preventive), DSS+Co (curative), and DSS (positive). Colitis was induced by the administration of 4% DSS in drinking water for 7 days. Co infusion (2 g/150 mL) was administered orally for 14 days. Clinical parameters, including body weight and the Disease Activity Index (DAI), were recorded. Oxidative stress markers, including myeloperoxidase (MPO), malondialdehyde (MDA), superoxide dismutase (SOD), catalase (CAT), reduced glutathione (GSH), and pro-inflammatory cytokines interleukin-6 (IL-6), tumor necrosis factor-alpha (TNF-α), and C-reactive protein (CRP), were assessed. DSS administration induced significant weight loss, inflammation, and colonic oxidative stress. Co infusion significantly attenuated these effects and reduced inflammatory and oxidative markers. The findings suggest that Co may have potential as a preventive and curative agent in IBD management.